IMPROVING NATURAL SCIENCE LEARNING OUTCOMES THROUGH IMAGE MEDIA FOR CLASS II STUDENTS - Sasanti, Nur Rohmah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The research was carried out at SD Negeri 1 Bengking with an implementation time of 2 meetings. The first meeting was on October 28, 2009 and the second meeting was on November 4, 2009. The science subject, sub-subject "I", was in class II, with a total of 17 students. This research uses an action research methodology that develops from one cycle to the next in a spiral manner. Planning, action, observation, and reflection are part of each cycle. The objectives to be achieved are as follows: (1) By involving students directly, it is hoped that students will pay attention to the lesson material, (2) through the question and answer method students can better understand the lesson material and not get bored, (3) the use of tools in the form of pictures can increase activity and student creativity. Conclusions that can be drawn include: (1) The use of discussion and question and answer methods through the media of pictures of plants and animals in learning can increase students' interest in learning in class II science subjects. (2) Actively involving students in the learning process. (3) Students are more enthusiastic about participating in learning because they are directly involved. (4) Learning will be more successful.